Migraine in Systemic Autoimmune Diseases - Cavestro, Cinzia; Ferrero, Marcella (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: Migraine and systemic autoimmune diseases are 2-3-fold more common in women and various studies have reported an association between the two pathologies. Methods: This review takes into account epidemiological studies involving migraine and systemic lupus erythematosus, antiphospholipid syndrome, Sjogren's syndrome, and other diffuse connective tissue diseases. This scientific literature analysis consists of the main articles found in Medline with a search up to April 2017. Results: Many epidemiological studies were carried out on patients suffering from systemic lupus erythematosus. Results showed that headache and migraine are more prevalent in systemic lupus erythematosus patients compared to controls, especially migraine with aura. Patients with Lupus and migraine show a higher lupus activity and association with Raynaud and/or antiphospholipids in these populations are contradictory. There are not enough data to establish an association between antiphospholipid syndrome and migraine. However, data are more consistent between antiphospholipid carrier condition and migraine. Systemic sclerosis is a rare disease, for this reason the amount of available data on this disorder are scanty. However, some studies reported an association between headache, migraine and systemic sclerosis, especially where gliotic brain lesions and Raynaud are coexisting. Finally, large propensity cohort population based studies suggested that systemic autoimmune diseases are more frequent in patients suffering from migraine. Conclusion: An attempt at explaining the possible link between these disorders and migraine is discussed at the end of the review. Several autoimmune alterations are shared by most autoimmune diseases and headache types. Endothelial dysfunction is the only alteration that is common among all these disorders.
Keywords: Migraine